Mobilespr app e mobilespr case: uma combinação de solução lógica e mecânica para sensores de ressonância de plasmons de superfície baseada em smartphones - Silva, Elizeu Sandro da (Universidade Federal Rural do Semi-Árido, 2021)
Optical sensors based on surface plasmon resonance (SPR - Surface Plasmon Ressonance), are devices used to analyze molecular interactions resulting from the resonant interaction of photons with free electrons, present in metallic materials. These sensors are powerful tools for performing the characterization of biomolecular interactions, as well as pathological agent detection, food quality, drug discovery and fuel quality applications. What limits them as field tools are their dimensions, the need to use an energy source and the need for sophisticated equipment. A growing and widely used trend is the use of portable platforms such as smartphones. These sensors have great technological power, such as high quality cameras, high performance processors and other features that make them attractive gadgets. In addition to having powerful operating systems that enable the user to use efficient and highly complex algorithms. Thus, in this work, the MobileSPR App and MobileSPR Case were developed, an integrated Mechanical Structure for Coupling and embedded software solution, based on the use of smartphones for surface plasmon resonance analysis, which can provide the researcher with flexibility in use in diverse environments. . The MobileSPR Case is characterized as a mechanical structure specially designed to contain all optical elements in the smartphone to file surface plasmon excitation. Made on a 3D printer, the case fits on top and is adjustable for various front-facing camera arrangements. Composed of two parts, it facilitates the smartphone replacement process, as well as enabling thinner and thicker biochips for surface plasmon excitation. The MobileSPR App, presented as a mobile application that controls the light source, camera, data process, displayed information and results storage, avoids extra components to create a portable SPR solution. The App allows the manipulation of light beams provided by the smartphone screen, which can vary between 380nm to 780nm, allowing use with biochips of different materials, metallic layer and configurations. The viability of the infrastructure was tested using a Xiaomi MI 9 Lite smartphone was used. Both a flat (thin) and trapezoidal (thicker) biochip operating at the angular interrogation were attached to the MobileSPR Case & App solution, and additional substances were explored experimentally
Keywords: Ressonância de plasmons de superfície; Smartphones; Infraestrutura baseada em smartphones; MobileSPR App; MobileSRP Case; Surface plasmon resonance; Smartphones; Infrastructure for biosensors; MobileSPR App; MobileSRP Case; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO